Implementation of Assessment of the Individual Attitudes of Santri at the Baitul Hidayah Islamic Boarding School - Taupikurrahman, Opik; Purnasari, Martina (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2023)
Nowadays, character and attitude are the main achievements in education, not only focusing on cognition, let alone Islamic religious education which has the main goal of forming students who have Islamic personalities (obedient, confident, and have noble character) both as individuals, families, communities, citizens and the world. To achieve this, it is necessary to instill strong morals and character in the individual students, especially students who are students who specifically deepen Islamic religious studies at Islamic boarding schools. Using the case study method by conducting interviews directly and accompanied by documents that are confirmed by literature review. To know this, it is necessary to carry out evaluation and research in the implementation of moral cultivation in individual students, so this concentration is what the author is studying to study the pattern of moral cultivation to achieve the goals of Islamic Religious Education itself.